Special Legal Procedures to Prevent the Exploitation of E-Commerce Transactions in Currency Smuggling and Money Laundering - Rashid, Sagban Khaleel; Saleh, Dalal Thamer (Journal of Ecohumanism, 2025)
Technical development has brought about many positives in the commercial field. Still, it has not been without negatives resulting from the misuse of modern technologies in commercial transactions illegally, perhaps the most prominent of which is the commission of currency smuggling and money laundering operations through electronic means, which have become one of the major challenges facing countries today. By exploiting modern electronic payment methods, and using cryptocurrencies such as Bitcoin is used to hide the identity of financial assets and make them easily transferable around the world. These currencies provide high confidentiality, making them attractive to criminals. In addition to the use of money transfer platforms, applications such as “Zelle” and “Venmo” are used to transfer illicit funds and hide them across multiple accounts, complicating investigators’ efforts to track the funds. E-commerce platforms are used to conduct quick transactions and hide illicit funds in minutes or even seconds. In addition, some exploit the foreign currency sales window and electronic payment cards to achieve their goals in this area .Since currency smuggling and money laundering have become a major threat to the national economy, they lead to: Decline in purchasing power: Currency smuggling leads to a decrease in the value of the national currency, which causes a decline in the purchasing power of citizens, Increase in poverty and crime: Decline in purchasing power leads to an increase in the poverty rate, which contributes to the spread of crimes such as theft and bribery, in addition to economic losses , as currency smuggling deprives the state of due taxes, which leads to large losses in the state budget, in addition to the occurrence of waves of inflation, as currency smuggling leads to an increase in the prices of goods and services, which increases inflation rates. Therefore, it was necessary for the legislator to develop advanced and flexible legislation aimed at confronting the misuse of means of technological development in currency smuggling and money laundering. It became necessary for the active banking authorities, headed by the central banks, to monitor, follow up and diagnose the new means invented by currency smugglers and money launderers in order to develop instructions and regulations that would limit these suspicious operations and protect the national economy.